Cerium doping of Ti-Al-N coatings for excellent thermal stability and oxidation resistance - Asanuma, H.; Polcik, P.; Kolozsvari, S.; Klimashin, F.F.; Riedl, H.; Mayrhofer, P.H. (Surface & coatings technology, 2017)
Ti–Al–N thin films are well established due to their outstanding thermo-mechanical properties. Nevertheless, this system is still a subject of many research activities to further enhance their oxidation resistance and thermal stability. The addition of reactive elements, such as Cerium, can significantly improve especially the oxidation resistance of various materials. Therefore, we study in detail the impact of Ce (2 at.% alloyed to powder metallurgically prepared Ti0.50Al0.50 targets) on growth processes, structure, mechanical properties, thermal stability, and oxidation resistance of magnetron sputtered Ti1−x−yAlxCeyN coatings prepared with DC bias potentials of Ubias=−25, −50, −75, and −100V. The deposition rate is significantly increased by a factor of ~1.75 (Ubias=−25V) to 1.45 (Ubias=−100V) when using Ti0.49Al0.49Ce0.02 instead of Ti0.50Al0.50 targets. Furthermore, also the hardness of the resulting single phase face centered cubic Ti0.43Al0.55Ce0.02N is with ~35GPa above that of Ti0.42Al0.58N with ~34GPa, for coatings on polycrystalline Al2O3 and Ubias=−50V. All temperature dependent characteristics of Ti0.42Al0.58N are improved significantly by the addition of Cerium. Wurtzite-structured AlN formation within Ti0.43Al0.55Ce0.02N can only be detected at Ta=1100°C, about 200°C higher as for Ti0.42Al0.58N. Their peak-hardness, due to spinodal decomposition of the supersaturated cubic phase is ~37.0GPa with Ta=900°C, as compared to 34.6GPa with Ta=800°C for Ti0.42Al0.58N. Additionally, even after exposure to ambient air at 950°C for 3h, still >50% of the Ti0.43Al0.55Ce0.02N coating is intact (below the ~1.2μm thin oxide scale), whereas Ti0.42Al0.58N is already fully oxidized. Based on our results we can conclude, that Ce-doping improves the deposition characteristics and mechanical properties as well as thermal stabilities (incl. oxidation resistance) of Ti–Al–N, to be used as protective coatings for a wide range of high-demanding applications. •Ce-doped Ti0.5Al0.5 targets allow for 1.75 higher deposition rates.•The hardness, as deposited as well as after annealing at 900°C, of Ti-Al-N is imporved by doping with Ce.•The formation of hexagonal AlN upon annealing, is postponed from 900 to 1100°C, by doping Ce to Ti-Al-N.•Ce allows for the formation of dense and well-adherent oxide scales, which can effectively retard the oxidation kinetics of Ti-Al-N.